Medicine as Culture: Indigenous Medicine in Cosmopolitan Mumbai - Leena Abraham (Economic & Political Weekly EPW april 18, 2009 vol xliv no 16, 2009)
Using the framework of medicine as culture and focusing on the indigenous medicine of ayurveda, this paper examines the relationship between health, culture and medicine, and its social reproduction in contemporary India. Specifically it deals with the cultural construct of "Kerala ayurveda", and the modes of its societal reproduction and recreation simultaneously as culture and as medicine in cosmopolitan Mumbai. Through an analysis of the historical and cultural roots of Kerala ayurveda and the role of community organisations in its translocation into a city, the paper shows the analytical fragility of the tradition/modern binary in the understanding of contemporary indigenous systems and questions the belief that state and market provide the foremost sites for institutional and secular practice of indigenous medicines